Karakterisasi Sifat Fisikokimia Sereal Berbasis Tepung Beras Merah Pecah Kulit - Sukarno Sukarno; Nova Kushandita; Slamet Budijanto (Jurnal Ilmu Pertanian Indonesia, 2020)
The purpose of this study was to formulate cereals from red rice, red beans, and sesame into the right food as a food consumed at breakfast and characterization of its physical chemistry. The cereal was made by extrusion method using an extruder with a temperature of 130°C and a rotating speed of auger, screw, and cutter 50 Hz. This study used a completely randomized design with 9 formulas. Based on the Bayes method, the best formula was F8 with a composition of brown red rice (85%), red beans (10%), and sesame (5%) cereals contained a total phenol compound of 0.10± 0.01 mg GAE/g, water content of 7.35±0.58%, ash content of 0.02±0.00%, protein content of 10.85±0.29%, fat content of 1.77±0.08, and carbohydrate content of 80.01±0.79%. Keywords: breakfast cereal, brown rice, red beans, red rice, sesame